THE ROLE OF SCIENTIFIC ETHICS IN THE DEVELOPMENT OF SCIENCE (Modern American Journal of Social Sciences and Humanities, 2026)
This article examines the role of scientific ethics in the development of science and scholarly activity. Scientific ethics is analyzed as a fundamental normative system that regulates researchers’ professional behavior, responsibility, honesty, objectivity, and social accountability. The study highlights the importance of ethical principles such as academic integrity, transparency, respect for intellectual property, and the prevention of scientific misconduct in ensuring sustainable scientific progress. Special attention is paid to the ethical challenges emerging in modern science under conditions of globalization, digitalization, and rapid technological advancement. The article argues that adherence to ethical standards not only enhances the credibility and reliability of scientific knowledge but also strengthens public trust in science and its institutions. Scientific ethics is therefore considered a key factor in fostering innovation, improving the quality of research, and guiding science toward socially beneficial outcomes.